Klasifikasi Jenis Kanker Prostat Melalui Citra MRI Menggunakan Pengolahan Citra Digital - Putra, Rangga Pahlevi; Marisa, Fitri (Universitas Merdeka Malang, 2024)
The prostate gland is one of the parts of the male reproductive system. The prostate gland is one of the organs that is not infrequently affected by cancer. Prostate cancer is one of the top diseases that often appears as one of the deadly diseases in the world. Including in Asia, the incidence of prostate cancer patients averages 7.21 per 100,000 men each year. To identify the symptoms of cancer, early detection in men can usually be done through a rectal examination. However, there is another method that utilizes imaging technology, specifically MRI images for prostate cancer, to determine the size of the cancer. By applying image processing methods such as Watershed segmentation and the Multiclass Support Vector Machine method, it is possible to classify the type of prostate cancer through MRI images. From the research conducted, it can be explained that the segmentation results of MRI images for prostate cancer using the Watershed method can show the detected cancer area spots. Meanwhile, the use of the MultiSVM method for classification shows an accuracy result of 90.166% for the polynomial kernel type.